2022
DOI: 10.3390/cryst12050748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Surface Structuring on Surface Wettability and Tribological Performance of Bulk Metallic Glass

Abstract: Bulk metallic glasses (BMGs) have been extremely popular in recent decades, owing to their superior properties. However, how to improve the surface functions and durability of BMGs has always been a key engineering issue. In this work, a facile laser-based surface structuring technique was developed for modulation and control of the surface functionalities of Zr-based BMG. For this technique, a laser beam was first irradiated on the surface to create periodic surface structure, followed by heat treatment to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It is found that the wear volume decreases with increasing annealing time as a result of improved elastic modulus or high H / E ratio and low friction coefficient. This will be the reason for the high wear resistance of materials . Researchers regarded that the real area of contact and material properties, such as microstructure, surface topography, and mechanical properties, are the key factors that govern the wear rate .…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the wear volume decreases with increasing annealing time as a result of improved elastic modulus or high H / E ratio and low friction coefficient. This will be the reason for the high wear resistance of materials . Researchers regarded that the real area of contact and material properties, such as microstructure, surface topography, and mechanical properties, are the key factors that govern the wear rate .…”
Section: Resultsmentioning
confidence: 99%
“…Laser surface structuring is a promising surface treatment technique with potential applications in various fields, including the automotive, biomedical, and electronics industries. It is a laser-based surface treatment process that can modify the surface of materials in a controlled manner [105] to create micro-and nanometric scale surface features, such as channels, pillars, and cavities, which can be used to improve the surface properties of materials, such as friction, wear, and adhesion. Various laser sources, such as picosecond (ps-), fs-, and ns-lasers, have been used for surface structuring [106].…”
Section: Laser Surface-structuring Processmentioning
confidence: 99%
“…[36][37][38] On the other hand, the concentration of Si is distinctly increased subsequent to the silicone oil-assisted heat treatment, which also indicates the deposition of hydrophobic silicon-based (PDMS) thin film onto the surface further enhancing the surface hydrophobicity. 33,[39][40][41] With the combined effects of these two chemical composition changes that notably affects the surface energy/wettability, superhydrophobicity…”
Section: Surface Chemistry Analysismentioning
confidence: 99%
“…Thirdly, for postprocess treatment, Dinh et al 21 utilized a conventional oven that costs for ∼$1k, while this work only requires a hot plate for $100. Lastly, as for chemical reagent, the general price of silane reagent is ∼$74 for 100 g, while the silicone oil only costs $3 for 100 g. Based on the above analyses, the laser-based surface functionalization process has the following advantages compared with other laser-based fabrication techniques: On the one hand, it utilizes more cost-effective UV nanosecond laser to texture glass sample, while UV laser can facilitate surface texturing with reduction of thermal effects and thus produce high-quality hierarchical surface micro/nanostructures comparable to those using ultrafast lasers 41 ; On the other hand, the post-process treatment for the laser-based surface functionalization process is significantly shortened, and the equipment and reagent costs are lowered as well. In conclusion, the laser-based surface functionalization process developed in this work exhibits the better overall process throughput in terms of both processing efficiency and cost effectiveness compared with the existing laser-based treatment methods for fabrication of superhydrophobic glass, demonstrating its strong potential for applications that superhydrophobic glass materials are essentially needed.…”
Section: Process Throughput Analysismentioning
confidence: 99%